A Novel Neutrosophic Weighted Extreme Learning Machine for Imbalanced Data Set - Akbulut, Yaman; Sengur, Abdulkadir; Guo, Yanhui; Smarandache, Florentin (Mdpi, 2017)
Extreme learning machine (ELM) is known as a kind of single-hidden layer feedforward network (SLFN), and has obtained considerable attention within the machine learning community and achieved various real-world applications. It has advantages such as good generalization performance, fast learning speed, and low computational cost. However, the ELM might have problems in the classification of imbalanced data sets. In this paper, we present a novel weighted ELM scheme based on neutrosophic set theory, denoted as neutrosophic weighted extreme learning machine (NWELM), in which neutrosophic c-means (NCM) clustering algorithm is used for the approximation of the output weights of the ELM. We also investigate and compare NWELM with several weighted algorithms. The proposed method demonstrates advantages to compare with the previous studies on benchmarks.
Keywords: extreme learning machine (ELM); weight; neutrosophic c-means (NCM); imbalanced data set